2019
DOI: 10.1002/advs.201900250
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Metal Nanoparticles Embedded in Conductive Metal–Organic Frameworks for Chemiresistors: Highly Active and Conductive Porous Materials

Abstract: Conductive porous materials having a high surface reactivity offer great promise for a broad range of applications. However, a general and scalable synthesis of such materials remains challenging. In this work, the facile synthesis of catalytic metal nanoparticles (NPs) embedded in 2D metal–organic frameworks (MOFs) is reported as highly active and conductive porous materials. After the assembly of 2D conductive MOFs (C‐MOFs), i.e., Cu3(hexahydroxytriphenylene)2 [Cu3(HHTP)2], Pd or Pt NPs are functionalized wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
61
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 60 publications
6
61
0
1
Order By: Relevance
“…These outstanding sensing performances outperform the current state-of-the-art 2D material-based NO2 chemiresistors operated at room temperature in air (Fig. 5 and Supplementary Table 8) 15,41,42,43,44,45,46,47,48,49,50 . To the best of our knowledge, the NO2 responses of our sensors are the highest among MOF-based NO2 sensors, and even superior to other 2D materials, including graphene, transition metal dichalcogenides (TMDs), and their composites.…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…These outstanding sensing performances outperform the current state-of-the-art 2D material-based NO2 chemiresistors operated at room temperature in air (Fig. 5 and Supplementary Table 8) 15,41,42,43,44,45,46,47,48,49,50 . To the best of our knowledge, the NO2 responses of our sensors are the highest among MOF-based NO2 sensors, and even superior to other 2D materials, including graphene, transition metal dichalcogenides (TMDs), and their composites.…”
mentioning
confidence: 77%
“…Comparing the HR-TEM images of Pt@Cu3(HHTP)2 made using conventional bulk synthesis technique 15 to that of MiCS (Supplementary Fig. 7) showed that the size variance of the Pt particles was much higher for the former.…”
mentioning
confidence: 99%
See 3 more Smart Citations